New Hope - Sorensen, Henri; Nang Chan Yeema (New York, USA Puffin Books, 1998)
Whenever Jimmy visits his grandfather he asks to hear about how Great-great-great grandfather Lars traveled with his family from Denmark to Minnesota and built a home that was the beginning of the town of New Hope.
Keywords: Juvenile Fiction